REDUCING STUDENTS’ READING ANXIETY BY USING SCAFFOLDED READING EXPERIENCE - Maximilian, Aksendro (LPPM STKIP PGRI Bandar Lampung, 2015)
One of the most important internal factors that influence students’ reading comprehension is the students’ foreign language learning anxiety. It will negativelly affect students’ reading ability. One of the sources of students’ reading anxiety is teaching method. The teachers of reading must use a various and interesting method. In this case, scaffolded reading experience is used to prove that it is one of the appropriate and interesting metod in teaching reading. This study aimed at finding the effectiveness of scaffolded reading experience to reduce students’ reading anxiety. For this purpose, the experimental research was done to the 60 tenth class students. Quantitative finding indicates that scaffolded reading anxiety is an effective method for reducing students’ reading anxiety. It is proven by the result of simple factorial design ANOVA 2X2. From the result of this research, the reseacher may conclude that scaffolded reading experience is an appropriate teaching method to reduce students reading anxiety. It can be applied in the reading class. By having a low reading anxiety, the students reading achievement could be increased optimally.